Depression Screening and Health Outcomes in Children and Adolescents: A Systematic Review. (December 2017) - Roseman, Michelle; Saadat, Nazanin; Riehm, Kira E.; Kloda, Lorie A.; Boruff, Jill; Ickowicz, Abel; Baltzer, Franziska; Katz, Laurence Y.; Patten, Scott B.; Rousseau, Cécile; Thombs, Brett D.
Objective: Depression screening among children and adolescents is controversial. In 2009, the United States Preventive Services Task Force first recommended routine depression screening for adolescents, and this recommendation was reiterated in 2016. However, no randomized controlled trials (RCTs) of screening were identified in the original 2009 systematic review or in an updated review through February 2015. The objective of this systematic review was to provide a current evaluation to determine whether there is evidence from RCTs that depression screening in childhood and adolescence improves depression outcomes. Method: Data sources included the MEDLINE, MEDLINE In-Process, EMBASE, PsycINFO, Cochrane CENTRAL and LILACS databases searched February 2, 2017. Eligible studies had to be RCTs that compared depression outcomes between children or adolescents aged 6 to 18 years who underwent depression screening and those who did not. Results: Of 552 unique title/abstracts, none received full-text review. No RCTs that investigated the effects of screening on depression outcomes in children or adolescents were identified. Conclusions: There is no direct RCT evidence that supports depression screening among children and adolescents. Groups that consider recommending screening should carefully consider potential harms, as well as the use of scarce health resources, that would occur with the implementation of screening programs.